A brief review of some important medicinal plants used in the treatment of asthma - Patel, Arshu P; Siddaiah, M. (Journal of Drug Delivery and Therapeutics, 2018)
Asthma is a common disease that is rising in prevalence worldwide with the highest prevalence in industrialized countries. Asthma affects about 300 million people worldwide and it has been estimated that a further 100 million will be affected by 2025. Ayurveda, Siddha, Unani and Folk (Tribal) medicines are the major systems of indigenous medicines. Over three-quarters of the world population relies mainly on plants and plant extracts for health care. Unlike many diseases, which can be attributed to the life style of modern man, asthma is an ancient illness. There are number of medicinal plants have been reported for antihistaminic/anti-asthmatic activities like Achyranthes aspera, Tephrosia purpurea, Dolichos lablab, Eclipta alba, Jasminum sambac, Balanites aegyptiaca, Viscum album, Tridex procumbens, Glycyrrhiza glabra and Cassia fistula. Present review is focused on used of medicinal plants for treatment of asthama. It is suggested that formulation and patent of the reported medicinal plants is mandatory for further use against asthma and if possible, clinical trials should be done of these plants for their appropriate use. Keywords: Medicinal plants, Asthma, Mast cells, Antihistaminic.